Metal ion doped cellulose-based aerogel, preparation method thereof and application of metal ion doped cellulose-based aerogel in deodorization and carbon reduction

By preparing the rice shell pad into a cellulose powder, and doping in the two -price metal ion solution, the metal ion doped cellulose base gas gel is prepared, which solves the existing fiber gas gel The problems of low selectivity and environmental pollution have achieved efficient and environmentally friendly greenhouse gas adsorption effects.

CN119331300APending Publication Date: 2025-01-21GUANGDONG INST OF MICROBIOLOGY GUANGDONG DETECTION CENT OF MICROBIOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411693947.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing cellulose aerogels have low selectivity in greenhouse gas adsorption and are average in adsorption, and the strong acids and crosslinking agents used in the preparation process produce large chemical waste, which is prone to cause secondary pollution in the environment.

Method used

By preparing the rice shell pad into a cellulose powder, and doped in the two -price metal ion solution, then mixed with polyvinyl alcohol, frozen and drying to prepare metal ions doped cellulose base gas gel.

Benefits of technology

It improves the porous structure and comparison area of ​​gas gel, enhances its physical and chemical adsorption, and improves the adsorption efficiency of greenhouse gas such as CO2, CH4 and N2O. At the same time, it reduces production costs, suitable Rice shell waste resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331300A_ABST
    Figure CN119331300A_ABST
Patent Text Reader

Abstract

The invention discloses metal ion doped cellulose-based aerogel, a preparation method thereof and application of the metal ion doped cellulose-based aerogel in deodorization and carbon reduction. The method comprises the following steps: drying rice husk padding, grinding, sequentially dissolving in pure water, alkali liquor and bleaching liquid, heating, stirring, repeatedly centrifuging, and drying precipitate to obtain rice husk cellulose powder; dissolving the rice husk cellulose powder in a divalent metal ion solution, fully mixing for 24-48 hours, and drying to obtain divalent metal ion doped cellulose powder; the divalent metal ion doped cellulose powder and a polyvinyl alcohol solution are homogenized, stirred and mixed to be uniform and then poured into a mold to be pre-frozen, then freeze drying is conducted, and the metal ion doped cellulose-based aerogel is obtained. The metal ion doped cellulose-based aerogel has a porous structure and a large specific surface area, so that the physical adsorption effect of the metal ion doped cellulose-based aerogel is improved, the active center of a catalyst is increased under the modification of metal ions, and the chemical adsorption effect of the metal ion doped cellulose-based aerogel is enhanced, so that the adsorption efficiency of greenhouse gases such as carbon dioxide, methane and nitrous oxide is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental protection management, and specifically relates to a metal ion-doped cellulose-based aerogel, a preparation method thereof, and an application thereof in deodorization and carbon reduction. Background Art

[0002] The increase in the demand for meat, eggs and milk among Chinese residents has driven the large-scale development of livestock and poultry farming. However, large-scale livestock and poultry farms face challenges in their green and low-carbon development, such as air quality, manure treatment and resource utilization. In order to reduce carbon emissions, it is necessary to reduce the greenhouse gases produced in the livestock and poultry farming process, mainly including carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O). Porous materials are an effective means to absorb greenhouse gases to reduce gas emissions. Among them, aerogels are an ideal porous material because they have a high specific surface area and high porosity and can provide numerous adsorption sites to increase gas adsorption capacity. However, aerogels that rely solely on physical adsorption have low selectivity for greenhouse gas adsorption and average adsorption capacity, which limits their widespread application. Therefore, the development of aerogel materials that effectively adsorb greenhouse gases and are environmentally friendly has attracted much attention.

[0003] Cellulose aerogel is an environmentally friendly biomass-based porous gel material with unique biocompatibility. It shows great potential in the field of gas adsorption, but there are still challenges in the development of this material. On the one hand, the solid waste formed by rice husk bedding as a planting matrix for livestock and poultry feed has not been fully utilized. However, it has high fiber content and excellent structure, and has the potential to prepare high-performance cellulose aerogel, but there is little research on greenhouse gas adsorption related research and application; on the other hand, the existing cellulose aerogel still needs to be optimized. For example, patent application CN118751212 discloses a visual aerogel for odor adsorption and its preparation method and application. The patent first modifies cellulose powder with strong acid, then modifies cellulose with organic amine and adds a cross-linking agent to form a hydrogel. The hydrogel is soaked in a copper salt solution and freeze-dried to form an aerogel, which can absorb gases such as volatile organic compounds, sulfides and nitrides. Although the cellulose aerogel invented in this patent adsorbs odorous gases through physical adsorption and chemical complexation, the chemical waste generated by the strong acid and cross-linking agent used in the preparation process is large, which is easy to cause secondary environmental pollution. Therefore, providing a material that can improve the resource utilization of rice husk waste in greenhouse gas adsorption and selectively adsorb greenhouse gases and a preparation method thereof is of great significance to the field of environmental governance technology and the green and low-carbon economic development of the poultry breeding industry. Summary of the invention

[0004] In view of the above-mentioned technical problems, the present invention provides a metal ion-doped cellulose-based aerogel, a preparation method thereof, and application thereof in deodorization and carbon reduction.

[0005] This is achieved through the following technical solutions:

[0006] The metal ion-doped cellulose-based aerogel of the present invention is prepared by the following preparation method, comprising the following steps:

[0007] 1) drying the rice husk bedding, grinding it into powder, dissolving it in pure water, alkali solution and bleaching solution in sequence, heating and stirring, repeatedly centrifuging, and drying the precipitate to obtain rice husk cellulose powder;

[0008] 2) dissolving rice husk cellulose powder in a divalent metal ion solution, mixing thoroughly for 24 hours to 48 hours, and drying to obtain divalent metal ion-doped cellulose powder;

[0009] 3) The divalent metal ion-doped cellulose powder and the polyvinyl alcohol solution are homogenously stirred and mixed, and then poured into a mold for pre-freezing, and then freeze-dried to obtain the metal ion-doped cellulose-based aerogel.

[0010] Furthermore, the weight ratio of the dry weight of the rice husk bedding and pure water in step 1) is 1:20 to 1:30, the heating temperature is 65 to 70° C., and the heating time is 1 to 2 hours.

[0011] Furthermore, the alkali solution in step 1) is a 4% sodium hydroxide solution, the weight ratio of the dry weight of the rice husk bedding to the alkali solution is 1:20-1:25, the heating temperature is 70-80° C., and the heating time is 2-3 hours.

[0012] Furthermore, the bleaching liquid described in step 1) is a mixed solution of sodium hydroxide, acetic acid and sodium hypochlorite, wherein the mass ratio of sodium hydroxide, acetic acid and sodium hypochlorite is 2.7:7.5:1; the weight ratio of the dry weight of the rice husk litter described in step 1) to the bleaching liquid is 1:80 to 1:120, the heating temperature is 80 to 90° C., and the heating time is 2 to 3 hours.

[0013] Furthermore, the divalent metal ion solution in step 2) includes copper sulfate, nickel chloride, cobalt chloride, zinc chloride or magnesium sulfate solution, and the concentration is 1 mol / L.

[0014] Furthermore, the weight ratio of the rice husk cellulose powder to the divalent metal ion solution in step 2) is 1:150 to 1:170.

[0015] Furthermore, in step 3), the weight ratio of the divalent metal ion-doped cellulose powder to the polyvinyl alcohol is 1:10 to 5:1.

[0016] Furthermore, step 3) is to homogenously stir and mix the divalent metal ion-doped cellulose powder and the polyvinyl alcohol solution, pour them into a polytetrafluoroethylene mold, pre-freeze them at -80°C for 12 hours, and then freeze-dry them at -60°C to obtain the metal ion-doped cellulose-based aerogel.

[0017] The present invention also provides a metal ion-doped cellulose-based aerogel prepared by the above method, which can be applied to the efficient and selective adsorption of greenhouse gases such as CO2, CH4 and N2O.

[0018] Advantages of the present invention:

[0019] (1) The porous structure and large specific surface area of ​​the metal ion-doped cellulose-based aerogel of the present invention increase its physical adsorption effect. In addition, the catalyst active centers are increased under the modification of metal ions, which enhances its chemical adsorption effect, thereby improving the adsorption efficiency of greenhouse gases such as carbon dioxide, methane and nitrous oxide;

[0020] (2) The metal ion-doped cellulose-based aerogel of the present invention has low production cost, simple preparation process, and is suitable for industrial application;

[0021] (3) The present invention utilizes rice husk waste as a resource, and effectively combines the resource utilization of solid waste with gas control and treatment, which is beneficial to the circular economy. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is the infrared spectra of the rice husk bedding, rice husk cellulose PC powder and nickel-doped cellulose-based aerogel in Example 5. DETAILED DESCRIPTION

[0023] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0024] Example 1

[0025] Step 1, placing the rice husk bedding in a drying oven at 60-65° C. for 24-48 hours and drying to constant weight, crushing it with a grinder and sieving it (40 meshes) to obtain rice husk powder;

[0026] Step 2, add 10 g of rice husk powder into 300 mL of deionized water and stir magnetically at 65° C. for 2 h. After cooling, centrifuge at 4° C. and 10,000 rpm for 15 min, remove the supernatant and take the precipitate;

[0027] Step 3, add the precipitate to 300 mL of 4% sodium hydroxide solution and stir magnetically at 70°C for 3 hours. After cooling, centrifuge at 4°C and 10,000 rpm for 15 minutes, remove the supernatant and take the precipitate. Repeat the above operation 3 times, and wash the precipitate repeatedly with deionized water until it is neutral;

[0028] Step 4, add the precipitate to 600 mL of bleaching solution and stir magnetically at 85°C for 3 hours. After cooling, centrifuge at 4°C and 10,000 rpm for 15 minutes, remove the supernatant and take the precipitate. Repeat the above operation twice, and wash the precipitate repeatedly with deionized water until it is neutral. The bleaching solution is prepared by first dissolving 8.1 g of sodium hydroxide and 22.5 mL of acetic acid in 300 mL of water and mixing evenly, and then mixing with 300 mL of 2% sodium hypochlorite solution by mass;

[0029] Step 5, drying the precipitate in an oven at 55° C. for 24 hours until constant weight is obtained to obtain rice husk cellulose PC powder;

[0030] Step 6, weighing 0.3 g of PC powder, adding it to 1 mol / L copper sulfate solution, standing for 48 hours, centrifuging to obtain a precipitate, and drying the precipitate in a 55° C. oven for 24 hours to constant weight to obtain nickel-doped cellulose Cu-PC powder;

[0031] Step 7, take 0.15g Cu-PC powder and add it to 15mL of 5% polyethylene glycol solution, stir and mix evenly, then pour it into a cylindrical polytetrafluoroethylene mold, put it into -80℃ pre-freeze for 12h, and freeze-dry it at a vacuum degree of 0Pa and a temperature of -60℃ for 48h to obtain copper-doped cellulose-based aerogel.

[0032] The copper-doped cellulose-based aerogel prepared in this embodiment has a CO2 adsorption capacity of 0.79 mmol / g, a CH4 adsorption capacity of 0.05 mmol / g, and a N2O adsorption capacity of 0.60 mmol / g at 0.1 MPa and 25°C.

[0033] Example 2

[0034] Step 1, placing the rice husk bedding in a drying oven at 60-65° C. for 24-48 hours and drying to constant weight, crushing it with a grinder and sieving it (40 meshes) to obtain rice husk powder;

[0035] Step 2, add 10 g of rice husk powder into 300 mL of deionized water and stir magnetically at 65° C. for 2 h. After cooling, centrifuge at 4° C. and 10,000 rpm for 15 min, remove the supernatant and take the precipitate;

[0036] Step 3, add the precipitate to 300 mL of 4% sodium hydroxide solution and stir magnetically at 70°C for 3 hours. After cooling, centrifuge at 4°C and 10,000 rpm for 15 minutes, remove the supernatant and take the precipitate. Repeat the above operation 3 times, and wash the precipitate repeatedly with deionized water until it is neutral;

[0037] Step 4, add the precipitate to 600 mL of bleaching solution and stir magnetically at 85°C for 3 hours. After cooling, centrifuge at 4°C and 10,000 rpm for 15 minutes, remove the supernatant and take the precipitate. Repeat the above operation twice, and wash the precipitate repeatedly with deionized water until it is neutral. The bleaching solution is prepared by first dissolving 8.1 g of sodium hydroxide and 22.5 mL of acetic acid in 300 mL of water and mixing evenly, and then mixing with 300 mL of 2% sodium hypochlorite solution by mass;

[0038] Step 5, drying the precipitate in an oven at 55° C. for 24 hours until constant weight is obtained to obtain rice husk cellulose PC powder;

[0039] Step 6, weighing 0.3 g of PC powder, adding it to 1 mol / L cobalt chloride solution, standing for 48 hours, centrifuging to obtain a precipitate, and drying the precipitate in a 55° C. oven for 24 hours to constant weight to obtain nickel-doped cellulose Co-PC powder;

[0040] Step 7, take 0.15g Co-PC powder and add it to 15mL of 5% polyethylene glycol solution, stir and mix evenly, then pour it into a cylindrical polytetrafluoroethylene mold, put it into -80℃ for pre-freezing for 12h, and freeze-dry it at a vacuum degree of 0Pa and a temperature of -60℃ for 48h to obtain cobalt-doped cellulose-based aerogel.

[0041] The cobalt-doped cellulose-based aerogel prepared in this example has a CO2 adsorption capacity of 1.08 mmol / g, a CH4 adsorption capacity of 0.24 mmol / g, and a N2O adsorption capacity of 0.80 mmol / g at 0.1 MPa and 25°C.

[0042] Example 3

[0043] Step 1, placing the rice husk bedding in a drying oven at 60-65° C. for 24-48 hours and drying to constant weight, crushing it with a grinder and sieving it (40 meshes) to obtain rice husk powder;

[0044] Step 2, add 10 g of rice husk powder into 300 mL of deionized water and stir magnetically at 65° C. for 2 h. After cooling, centrifuge at 4° C. and 10,000 rpm for 15 min, remove the supernatant and take the precipitate;

[0045] Step 3, add the precipitate to 300 mL of 4% sodium hydroxide solution and stir magnetically at 70°C for 3 hours. After cooling, centrifuge at 4°C and 10,000 rpm for 15 minutes, remove the supernatant and take the precipitate. Repeat the above operation 3 times, and wash the precipitate repeatedly with deionized water until it is neutral;

[0046] Step 4, add the precipitate to 600 mL of bleaching solution and stir magnetically at 85°C for 3 hours. After cooling, centrifuge at 4°C and 10,000 rpm for 15 minutes, remove the supernatant and take the precipitate. Repeat the above operation twice, and wash the precipitate repeatedly with deionized water until it is neutral. The bleaching solution is prepared by first dissolving 8.1 g of sodium hydroxide and 22.5 mL of acetic acid in 300 mL of water and mixing evenly, and then mixing with 300 mL of 2% sodium hypochlorite solution by mass;

[0047] Step 5, drying the precipitate in an oven at 55° C. for 24 hours until constant weight is obtained to obtain rice husk cellulose PC powder;

[0048] Step 6, weighing 0.3 g of PC powder, adding it to 1 mol / L magnesium sulfate solution, standing for 48 hours, centrifuging to obtain a precipitate, and drying the precipitate in a 55° C. oven for 24 hours to constant weight to obtain nickel-doped cellulose Mg-PC powder;

[0049] Step 7, take 0.15g Mg-PC powder and add it to 15mL of 5% polyethylene glycol solution, stir and mix evenly, then pour it into a cylindrical polytetrafluoroethylene mold, put it into -80℃ for pre-freezing for 12h, and freeze-dry it at a vacuum degree of 0Pa and a temperature of -60℃ for 48h to obtain magnesium-doped cellulose-based aerogel.

[0050] The magnesium-doped cellulose-based aerogel prepared in this embodiment has a CO2 adsorption capacity of 0.73 mmol / g, a CH4 adsorption capacity of 0.39 mmol / g, and a N2O adsorption capacity of 0.87 mmol / g at 0.1 MPa and 25°C.

[0051] Example 4

[0052] Step 1, placing the rice husk bedding in a drying oven at 60-65° C. for 24-48 hours and drying to constant weight, crushing it with a grinder and sieving it (40 meshes) to obtain rice husk powder;

[0053] Step 2, add 10 g of rice husk powder into 300 mL of deionized water and stir magnetically at 65° C. for 2 h. After cooling, centrifuge at 4° C. and 10,000 rpm for 15 min, remove the supernatant and take the precipitate;

[0054] Step 3, add the precipitate to 300 mL of 4% sodium hydroxide solution and stir magnetically at 70°C for 3 hours. After cooling, centrifuge at 4°C and 10,000 rpm for 15 minutes, remove the supernatant and take the precipitate. Repeat the above operation 3 times, and wash the precipitate repeatedly with deionized water until it is neutral;

[0055] Step 4, add the precipitate to 600 mL of bleaching solution and stir magnetically at 85°C for 3 hours. After cooling, centrifuge at 4°C and 10,000 rpm for 15 minutes, remove the supernatant and take the precipitate. Repeat the above operation twice, and wash the precipitate repeatedly with deionized water until it is neutral. The bleaching solution is prepared by first dissolving 8.1 g of sodium hydroxide and 22.5 mL of acetic acid in 300 mL of water and mixing evenly, and then mixing with 300 mL of 2% sodium hypochlorite solution by mass;

[0056] Step 5, drying the precipitate in an oven at 55° C. for 24 hours until constant weight is obtained to obtain rice husk cellulose PC powder;

[0057] Step 6, weighing 0.3 g of PC powder, adding it to 1 mol / L nickel chloride solution, standing for 48 hours, centrifuging to obtain a precipitate, and drying the precipitate in an oven at 55° C. for 24 hours to constant weight to obtain nickel-doped cellulose Ni-PC powder;

[0058] Step 7, take 0.15g Ni-PC powder and add it to 15mL of 5% polyethylene glycol solution, stir and mix evenly, then pour it into a cylindrical polytetrafluoroethylene mold, pre-freeze it at -80℃ for 12h, and freeze-dry it at a vacuum degree of 0Pa and a temperature of -60℃ for 48h to obtain nickel-doped cellulose-based aerogel.

[0059] The nickel-doped cellulose-based aerogel prepared in this embodiment has a CO2 adsorption capacity of 1.46 mmol / g, a CH4 adsorption capacity of 1.49 mmol / g, and a N2O adsorption capacity of 1.97 mmol / g at 0.1 MPa and 25°C.

[0060] Example 5

[0061] Step 1, placing the rice husk bedding in a drying oven at 60-65° C. for 24-48 hours and drying to constant weight, crushing it with a grinder and sieving it (40 meshes) to obtain rice husk powder;

[0062] Step 2, add 10 g of rice husk powder into 300 mL of deionized water and stir magnetically at 65° C. for 2 h. After cooling, centrifuge at 4° C. and 10,000 rpm for 15 min, remove the supernatant and take the precipitate;

[0063] Step 3, add the precipitate to 300 mL of 4% sodium hydroxide solution and stir magnetically at 70°C for 3 hours. After cooling, centrifuge at 4°C and 10,000 rpm for 15 minutes, remove the supernatant and take the precipitate. Repeat the above operation 3 times, and wash the precipitate repeatedly with deionized water until it is neutral;

[0064] Step 4, add the precipitate to 600 mL of bleaching solution and stir magnetically at 85°C for 3 hours. After cooling, centrifuge at 4°C and 10,000 rpm for 15 minutes, remove the supernatant and take the precipitate. Repeat the above operation twice, and wash the precipitate repeatedly with deionized water until it is neutral. The bleaching solution is prepared by first dissolving 8.1 g of sodium hydroxide and 22.5 mL of acetic acid in 300 mL of water and mixing evenly, and then mixing with 300 mL of 2% sodium hypochlorite solution by mass;

[0065] Step 5, drying the precipitate in an oven at 55° C. for 24 hours until constant weight is obtained to obtain rice husk cellulose PC powder;

[0066] Step 6, weighing 0.3 g of PC powder, adding it to 1 mol / L nickel chloride solution, standing for 48 hours, centrifuging to obtain a precipitate, and drying the precipitate in an oven at 55° C. for 24 hours to constant weight to obtain nickel-doped cellulose Ni-PC powder;

[0067] Step 7, take 0.3g Ni-PC powder and add it to 15mL of 5% polyethylene glycol solution, stir and mix evenly, then pour it into a cylindrical polytetrafluoroethylene mold, put it into -80℃ for pre-freezing for 12h, and freeze-dry it at a vacuum degree of 0Pa and a temperature of -60℃ for 48h to obtain nickel-doped cellulose-based aerogel.

[0068] The nickel-doped cellulose-based aerogel prepared in this embodiment has a CO2 adsorption capacity of 4.85 mmol / g, a CH4 adsorption capacity of 2.48 mmol / g, and a N2O adsorption capacity of 2.03 mmol / g at 0.1 MPa and 25°C.

Claims

1. A method for preparing metal ion-doped cellulose-based aerogel, characterized in that: The following steps are involved: 1) drying the rice husk bedding, grinding it into powder, dissolving it in pure water, alkali solution and bleaching solution in sequence, heating and stirring, repeatedly centrifuging, and drying the precipitate to obtain rice husk cellulose powder; 2) dissolving rice husk cellulose powder in a divalent metal ion solution, mixing thoroughly for 24 hours to 48 hours, and drying to obtain divalent metal ion-doped cellulose powder; 3) The divalent metal ion-doped cellulose powder and the polyvinyl alcohol solution are homogenously stirred and mixed, and then poured into a mold for pre-freezing, and then freeze-dried to obtain the metal ion-doped cellulose-based aerogel.

2. The preparation method according to claim 1, characterized in that: The weight ratio of the dry weight of the rice husk bedding and pure water in step 1) is 1:20-1:30, the heating temperature is 65-70° C., and the heating time is 1-2 hours.

3. The preparation method according to claim 1, characterized in that: The alkali solution in step 1) is a 4% sodium hydroxide solution, the weight ratio of the dry weight of the rice husk bedding to the alkali solution is 1:20-1:25, the heating temperature is 70-80° C., and the heating time is 2-3 hours.

4. The preparation method according to claim 1, characterized in that: The bleaching liquid described in step 1) is a mixed solution of sodium hydroxide, acetic acid and sodium hypochlorite. Preferably, the mass ratio of sodium hydroxide, acetic acid and sodium hypochlorite is 2.7:7.5:1; preferably, the weight ratio of the dry weight of the rice husk bedding described in step 1) to the bleaching liquid is 1:80-1:120, the heating temperature is 80-90°C, and the heating time is 2-3h.

5. The preparation method according to claim 1, characterized in that: The divalent metal ion solution described in step 2) includes copper sulfate, nickel chloride, cobalt chloride, zinc chloride or magnesium sulfate solution, preferably, with a concentration of 1 mol / L.

6. The preparation method according to claim 1, characterized in that: The weight ratio of the rice husk cellulose powder to the divalent metal ion solution in step 2) is 1:150 to 1:

170.

7. The preparation method according to claim 1, characterized in that: In step 3), the weight ratio of the divalent metal ion-doped cellulose powder to polyvinyl alcohol is 1:10 to 5:

1.

8. The preparation method according to claim 1, characterized in that: Step 3) is to homogenously stir and mix the divalent metal ion-doped cellulose powder and the polyvinyl alcohol solution, pour them into a polytetrafluoroethylene mold, pre-freeze them at -80°C for 12 hours, and then freeze-dry them at -60°C to obtain the metal ion-doped cellulose-based aerogel.

9. A metal ion-doped cellulose-based aerogel prepared according to any one of the preparation methods of claims 1-8.

10. Use of the metal ion-doped cellulose-based aerogel according to claim 9 in the adsorption of CO2, CH4 and / or N2O.